The nations in the divine economy Paul's covenantal hermeneutics and participation in Christ - Campbell, William S. ca. 20./21. Jh. (Lanham Lexington Books/Fortress Academic, 2018)
Reimagining the period of Christian origins -- The hermeneutics of antithesis: the reception of Paul in contrast to Judaism -- Universality via particularity -- Association and interaction with Judaism by Paul and his communities -- Paul and the recognition of ethnic distinctiveness -- The hermeneutics of commonality and comparison in 2 Corinthians 3 -- The faithfulness of God, the remnant, and the ethnē -- Ethnē in Christ and their relation to Israel -- Participation in Christ and the transformation of identity -- Covenantal hermeneutics in Paul.
Although covenant language is not prominent in Paul's letters, Campbell argues that it remains the basis of his thought in differentiated ways concerning Israel and the nations. The covenant remains God's covenant with Israel, but through its re-ratification in Christ, non-Jews participate in the Abrahamic promises
Includes bibliographical references (pages 355-385) and indexes
Keywords: Paul -- the Apostle, Saint; Paul; Bible -- Theology; Bible -- Criticism, interpretation, etc; Bible; Covenant Theology; Identification (religion); Theology; Criticism, interpretation, etc